(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The development of a future mechanism for sustainable development in Iraq to meet the current and future challenges requires an analysis of the indicators of sustainable development. This research aims at presenting and analyzing the social care aspect and highlighting the important role of taxes with a focus on social sustainable development to determine the extent and direction of changes. Level of progress, the researcher concludes the weakness of the financial allocations to the Ministry of Labor and Social Affairs and in line with the large number of people who apply the conditions and controls, and recommends the researcher the necessity of participation of all segments of society between the public and private sector In terms of objectives and programs in accordance with the real needs of society and the formulation of tax policy in order to activate the role of tax policy in achieving development and enhancing opportunities for social justice.